Contribution of Entrepreneurial Characteristics and Competency towards Business Performance of the Japan Internship Alumni Association - Ahmad Syariful Jamil; Resti Prastika Destiarni; Ahmad Zainuddin (Fakultas Pertanian, Universitas Timor, 2022)
The main objective of the Japan internship program for young farmers is to address farmer regeneration problems in Indonesia. In other words, young farmers joining the program in Japan could gain knowledge and experience related to advanced technology, then after returning to Indonesia they could implement those skills to be entrepreneurs. Therefore, the objectives of this study were: 1) to describe the characteristics of Japan internship alumni; and 2) to analyze the contribution of individual, psychological characteristics and entrepreneurial competence toward business performance of the Japan internship alumni association. Purposive sampling approach was used to determine the respondents in this study with the number of respondents as many as 123 people. Respondents were spread from 3 provinces in Java Island, namely West Java, Central Java, and East Java. Data collection was carried out from November 2020 to March 2021. In order to answer the research objectives, path analysis was used as the basis for analyzing the contribution of individual and psychological characteristics and entrepreneurial competence to the business performance. In this research, it can be seen that there was significant influence of both individual and psychological characteristics toward entrepreneurial competency. In addition, entrepreneurial characteristic variables had both a direct and indirect influence on performance. Entrepreneurial competence also had a positive influence on business performance. This reflects that after returning to Indonesia, respondents had personalities that shape entrepreneurial competencies. In this case, these competencies can ultimately drive business performance. Thus, the Japan internship program had been able to shape individual and psychological characteristics that were able to improve entrepreneurial competence and business performance at the same time.